2018
DOI: 10.1038/s41598-018-21690-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiling of poorly differentiated sinonasal tumours

Abstract: The sinonasal cavities harbour a variety of rare tumour types. Many carry a poor prognosis while therapeutic options are limited. Histopathological classification can be difficult, especially for poorly differentiated tumours such as olfactory neuroblastoma (ONB), sinonasal neuroendocrine carcinoma (SNEC) and sinonasal undifferentiated carcinoma (SNUC). We analysed Affymetrix OncoScan genome-wide copy number profiles of these three tumour types, both as originally diagnosed and as regrouped by their cytokerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…A similar overlap in copy number alterations between neuroendocrine carcinoma of the salivary gland a lung has also been reported . Similarly, only few data on the mutational landscape of olfactory neuroblastoma are available with preferential affection of TP53 and a heterogeneous pattern of copy‐number alterations .…”
Section: Tumors Of the Sinonasal Tractsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar overlap in copy number alterations between neuroendocrine carcinoma of the salivary gland a lung has also been reported . Similarly, only few data on the mutational landscape of olfactory neuroblastoma are available with preferential affection of TP53 and a heterogeneous pattern of copy‐number alterations .…”
Section: Tumors Of the Sinonasal Tractsupporting
confidence: 60%
“…Data on the molecular features of olfactory neuroblastoma and sinonasal neuroendocrine carcinoma (SNEC) are limited. In small cell SNEC, the pattern of copy-number alterations is complex and genetics seem to show overlap with small cell neuroendocrine carcinoma of the lung with mutations of TP53 and RB1, upregulation of BCL2 signaling, and activation of MYC and PI3K pathways (86,92). A similar overlap in copy number alterations between neuroendocrine carcinoma of the salivary gland a lung has also been reported (93).…”
Section: Smarcb1-deficient Sinonasal Carcinoma Often Show Either Hetementioning
confidence: 74%
“…The use of molecular biology techniques is, at the present time, of great help to characterise these tumours in a more precise way. 32,33 Indeed, pathology appears to be the most important predictor of five-year survival. 34 These new diagnostic entities are well-defined in terms of their underlying aetiology, which holds promise for the development of novel therapeutic targets.…”
Section: Resultsmentioning
confidence: 99%
“…Few comprehensive molecular studies have been conducted to date, the majority of which look at multiple tumour types. Lopez and co-workers' classification of subtype based on specific marker expression and copy number alterations demonstrated that SNECs typically stain positive for both cytokeratin and neuroendocrine markers, in contrast to SNUCs and ONBs and exhibit many copy number alterations with a high level of chromosomal instability [54]. In another study assessing the status of MiR-21 as a potential prognostic marker, the authors found that the marker was upregulated in their tumour cohort, which consisted of a small minority of SNECs [55].…”
Section: Novel Biomarkers In Sinonasal Neuroendocrine Carcinomamentioning
confidence: 99%